Metila To Tepokona: Islam and Community-Based Wisdom of Tolerance in Southeast Sulawesi Society - Arsyad, Abdul Rahman; Amiruddin; Hasanuddin (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Religious harmony in Indonesia is frequently analyzed from a liberal viewpoint, emphasizing individual rights and freedom. However, this perspective does not always reflect the social realities of communal societies in Indonesia, including South East Sulawesi, where tolerance is built on communalism rather than individual liberty. This article explores a tolerance practice called "Metila To Tepokona” (our brothers are harmonious), a local wisdom rooted in the historical interplay between Islam and local culture, functioning as a communal mechanism for social harmony. It centers social ethics on the community instead of personal liberty, promoting values of unity, moral duty, and respect for diversity. These values result from the interaction between Islamic principles and cultural practices that emphasize social cohesion. Based on qualitative research with interviews and observations, the article shows that this wisdom underpins tolerance among different Islamic sects and religions, viewing each other as brothers. For unity, people must embrace a communal ethic—respecting diverse groups not because of individual freedoms but because of their capacity for community brotherhood. "Metila To Tepokona" thus offers an alternative model of tolerance rooted in communalism, providing insights into harmony beyond liberalism.